ROSACEA AND CHRONIC VENOUS DISEASE: COMORBIDITY PATTERNS AND HEREDITARY RISK - Asiri, Sultan Zuhair Ali; Melekhovets, Oksana; Lobatiuk, Mariia; Melekhovets, Iurii (Eastern Ukrainian Medical Journal, 2026)
Introduction. The pathophysiology of rosacea is driven by complex interactions involving dysregulation of the immune system, neurogenic inflammation, and vascular hyperreactivity. Parallel to this, the hallmark of chronic venous disease (CVD) pathophysiology likely remains in inflammation, possibly triggered by sustained venous hypertension and valvular incompetence. No reliable epidemiological data on comorbidity rosacea with CVD were found in the literature. The aim was to study the comorbidity of rosacea with chronic venous disease and to determine the impact of positive rosacea and chronic venous disease family anamnesis as risk factors for rosacea using the logistic regression model with the goals of sustainable development, namely, ensuring good health and well-being. Materials and Methods. A total of 245 individuals were enrolled in the study and allocated between two groups. Rosacea Group included 141 patients who were eligible diagnostic criteria for rosacea [5]. Control Group included 104 participants who have been consulting by a GPs about a healthy lifestyle and had no clinical signs of the Rosacea disease. The mean age of patients in the Control Group was 45.84 ± 14.47 years, in the Rosacea Group it was 44.46 ± 11.26 years. No statistically significant difference was found between the groups (Welch t = 0.806; df = 188; p = 0.421). These findings indicate that age distribution was comparable in both cohorts. To proof the evidence of comorbidity Rosacea with Chronic Venous Disease we assess potential risk factors for the development of rosacea, the presence of Chronic Venous Disease (CVD), rosacea family history (positive family history of rosacea), and CVD family history (positive family history of CVD) were analyzed. Statistical data analysis was performed using the free software JASP (Version XX, University of Amsterdam, Netherlands). Descriptive statistics were used to assess the age characteristics of the sample; the Bayesian Binomial Test was used to assess the frequency of clinical signs and anamnestic factors; and the Binary Logistic Regression method was used to calculate the association between risk factors and the probability of developing rosacea. Results and Discussion. It was found that CVD was detected in 40.8% of patients (n=100), a positive family history of rosacea was identified in 26.9% of patients (n=66), and a positive family history of CVD in 23.3% (n=57) of respondents. Regression analysis demonstrated statistically significant associations between rosacea and all investigated predictors. The presence of CVD was associated with substantially increased odds of rosacea development (OR = 3.570; 95% CI: 1.987–6.417; p < 0.001). Family history of rosacea showed the strongest relationship with disease occurrence (OR = 4.399; 95% CI: 2.172–8.909; p < 0.001). This observation indicates a pronounced hereditary component in rosacea susceptibility. A positive family history of Chronic Venous Disease was also independently associated with rosacea (OR = 2.342; 95% CI: 1.189–4.615; p = 0.014). Numerous scientific researches on the comorbidity of rosacea emphasise the significance of this disease and do not limit rosacea only to skin manifestations, considering it within the framework of the exposome theory. Our data confirm the influence of genetic and epigenetic factors (family health history, positive with rosacea or CVD, concomitant rosacea with CVD) on the incidence of rosacea, which can be used in clinical practice for making prognosis and prescribing appropriate treatment with the goals of sustainable development, namely, ensuring good health and well-being.